piRNAs Regulated by Mitochondria Variation Linked With Reproduction and Aging in Caenorhabditis elegans - Zhu, Zuobin; Li, Ying; Liang, Mengyu; Wang, Lei; Wang, Liang; Rizak, Joshua D.; Han, Conghui; Zhang, Wenda (Frontiers in Genetics, 2020)
In C. elegans, the binding of Piwi protein to a non-coding RNA form, called piRNA, has been found to be important to both reproductive and aging processes. As the biosynthesis of piRNA is modulated by mitochondrial function, it is likely that the interaction between mitochondrial function and piRNA expression plays an unknown, yet important, role in reproductive and aging processes because both processes are known to affected by declines in mitochondrial quality and activity. While the relationship between reproduction and longevity is not characterized in full, the optimality theory of aging and the disposable soma theory suggest that a trade-off between energy and resources is needed for reproductive and aging maintenance. In this study, the influence of mitochondrial variations, via a respiratory chain complex IV (COX1) polymorphism, on piRNA expression was examined in relation to the reproductive and aging outcomes of C. elegans. The COX1 polymorphism in mitochondria was found to affect the number of piRNAs expressed, the development of germ cells and the length of the lifespan of the nematodes. Interestingly, more than two-thirds of the piRNA expression changes associated to the mitochondrial variation were found to also be affected by age. A gene ontology (GO) analyses of the altered piRNA species found that the piRNAs affected by mitochondrial variation and age were linked to genes known to have roles in reproductive and developmental function. Moreover, a piRNA-lncRNA-mRNA regulatory network based on the differential expression patterns of piRNA related to the mitochondrial variation was constructed to further identify potential gene targets with functional interactions. Similarly, this network identified genes involved in reproduction, development and aging processes. These findings provide new insight into understanding how mitochondrial variations may regulate piRNA expression and may influence the underlying molecular mechanisms that affect reproduction and aging.